Bulky 9-phenylfluorene fuctionalized 2, 6-bis(N-carbazolyl)- pyridine with high triplet energy level as host for blue thermally activated delayed fluorescence devices. (April 2020) - Zhao, Xiang-Hua; Han, Chun-Miao; Li, Yue; Bai, Ming-Gui; Yang, Jin-Can; Xu, Hui; Yuan, Shun-Dong; Xie, Ling-Hai; Xu, Zhi-Jie
Abstract: A new 9-phenylfluorene functionalized 2, 6-bis( N -carbazolyl)-pyridine compound 2, 6-bis(3-(9-phenyl-fluoren- 9-yl)-carbazol-9-yl)pyridine (2, 6-PFCzPy ) with large steric hindrance and high triplet energy level has been successfully prepared by introducing 3-(9-phenyl-fluoren-9-yl)-carbazole unit into the 2, 6-position of pyridine group via Ullmann reaction. Cyclic voltammetry (CV) was used to study the electrochemical properties of the compound and obtain HOMO (−5.85 eV), LUMO (−2.09 eV), and energy gap (Eg, 3.57 eV). The 2, 6-CzPy-based compound was employed as host to fabricate blue thermally activated delayed fluorescence (TADF) organic light-emitting diodes (OLEDs) for the first time with the maximum EQEs of 6.2% at the doping concentration as high as 30%. The electroluminescent (EL) spectra show almost no changes along with the driving voltage ranging from 5.1 to 15.1 V at high doping concentration, which indicates the 2, 6-CzPy-based three dimensional bulky compound could successfully suppress the excimer emission of the guest in high doping ratio. Graphical abstract: The first 2, 6-bis( N -carbazolyl)-pyridine-based compound with large steric hindrance was employed as host for blue TADF OLEDs with stable EL spectrum under different driving voltages at doping concentration as high as 30%. Image 1 Highlights: The first 2, 6-bis( N -carbazolyl)-pyridine-based compound with large steric hindrance was used as host for blue TADF OLEDs. Stable blue EL spectra were achieved under different driving voltages at high doping concentration of 30%. The enhanced thermal and morphological stability was achieved with high triplet energy level (T1, 2.83 eV) and controllable electrochemical properties.